Guards and decoys: RIPoptosome and inflammasome pathway regulators of bacterial effector-triggered immunity. - Haleema Sadia Malik; James B Bliska (PLoS Pathogens)
Virulent microbes produce proteins that interact with host cell targets to promote pathogenesis. For example, virulent bacterial pathogens have proteins called effectors that are typically enzymes and are secreted into host cells. To detect and respond to the activities of effectors, diverse phyla of host organisms evolved effector-triggered immunity (ETI). In ETI, effectors are often sensed indirectly by detection of their virulence activities in host cells. ETI mechanisms can be complex and involve several classes of host proteins. Guards monitor the functional or physical integrity of another host protein, the guardee or decoy, and become activated to initiate an immune response when the guardee or decoy is modified or disrupted by an effector. A guardee typically has an intrinsic anti-pathogen function and is the intended target of an effector. A decoy structurally mimics a host protein that has intrinsic anti-pathogen activity and is unintentionally targeted by an effector. A decoy can be an individual protein, or a protein domain integrated into a guard. Here, we review the origins of ETI and focus on 5 mechanisms, in which the key steps of a pathway can include activation of a caspase by a RIPoptosome or inflammasome, formation of pores in the plasma membrane, release of cytokines and ending in cell death by pyroptosis. Survey of the 5 mechanisms, which have been shown to be host protective in mouse models of bacterial infection, reveal how distinct regulators of RIPoptosome or inflammasome pathways can act as guards or integrated decoys to trigger ETI. Common themes are highlighted and the limited mechanistic understanding of ETI bactericidal activity is discussed.